Design of Smart Identification Infrastructure for Presence System - Ryana Suchendra, Devie; Priagung Wicaksono, Mukti; ., Periyadi (International Journal of Engineering and Technology, 2019)
The importance of attendance system is the processing speed of data collection, writing the presence data and summary of report. Currently Presence system takes a long time to record the user's presence. The problem occurs for several reasons, one of which is caused by the design of the network infrastructure. This problem can slow the process of collecting data on attendance system. In this research will be designed a prototype of network infrastructure as one of the alternative technologies for the presence system. This infrastructure will utilize the existing MAC Address on mobile devices used by the user to be able to use the system's presence. This network system can recognize all the MAC addresses connected to the access point (SSSID) as a unique identification for each user who is connected. the process of collecting MAC Address obtained by manipulating the outcome of the application Airodump-ng using the command shell programming. in the end the results obtained by using this infrastructure system can read 22 users at the same time in an average time of 2.2 minutes and the CPU and RAM usage from the server shows that the server load take 50% less each CPU from 4 CPU while RAM that being used is 7.2% from 100%. On Access Point device CPU and memory usage is low the value of 2% and 71% for its free RAM.Â Â